Effect of dietary seaweed extract supplementation on growth, feed utilization, hematological indices, and non-specific immunity of Nile Tilapia, Oreochromis niloticus challenged with Aeromonas hydrophila - Mohamed Ashour (2020)
© 2020, Springer Nature B.V. Seaweeds have increasing importance because of their bioactive compounds and their potential application in different industries. Liquid seaweed extract are commercially used as an agricultural biofertilizer. The current work investigated the potential of a commercial liquid seaweed extract, named TrueAlgaeMax (TAM), as a diet feed additive for Nile tilapia Oreochromis niloticus. Five diets (D0, D0.5, D1, D1.5, and D2) were supplemented with different TAM concentrations (0, 0.5, 1, 1.5, and 2%, respectively) to investigate the growth performance, feed utilization, and non-specific immunity of O. niloticus challenged with Aeromonas hydrophila. Healthy mono-sex O. niloticus fingerlings were randomly stocked for 70 days in net enclosures (3 m × 6 m × 1 m) at a density of 20 fish m−3 with an average initial body weight of 50 g fingerling−1 (three groups for each treatment with a total of 1080 fish per treatment). Diet D2 represented the highest weight gain (WG) value (161.29 g), average daily weight gain (ADWG) value (2.30 g day−1), and specific growth rate (SGR) value (2.40% day−1) and achieved the best feed conversion ratio (FCR) value (1.31). In addition, D2 achieved the highest serum protein (5.47 g dL−1), lysozyme (3.75 μg mL−1), and respiratory burst activity (1.89 mg mL−1). Fish mortality decreased by increasing TAM levels. The GC-Mass data of TAM showed nine main phytochemical compounds belonging to seven different important bioactive groups reported as immunity enhancer and growth promoting and showed antioxidant and antimicrobial properties. The results recommended that increasing the levels of TAM up to 2% as feed additive for O. niloticus diet strongly enhances growth performance, feed utilization, and non-specific immunity of Nile tilapia O. niloticus challenged with A. hydrophila. Considering seaweed additions (dry weight or extract) as aquaculture feed additive is of importance.